Apprenticeship training in Denmark : the impacts of subsidies - Westergard-Nielsen, Niels [Verfasser]; Rasmussen, Anders Rue [Verfasser] (My University, 1997)
"For years, Denmark has maintained and developed its apprenticeship system which is comparable to the German system. Today, about 40% of the youth cohorts get apprenticeship training. The paper describes the basic functioning of the labour market of apprentices. It is initially ahown how the wage and unemployment rates of skilled workers who served an apprenticeship differ from those of non- skilled workers. In recent years there have been periods with serious mismatches between the demand for and the supply of apprenticeships. Through the 80s subsidies were introduced to overcome this shortage. The main purpose of this paper is to investigade the possible impact of these subsidies. A unique longitudinal data set that enables us to follow 1 000 work places from 1980 to 1991 is applied. This makes it possible to control for observed and unobserved work place effects. The estimates show that the subsidies have had an impact on the supply of places in some industries while others are not affected at all. The total effect has been compared to the costs and it is found that the total costs per extra apprenticeship is about 54,000 DKK. Finally, the results are used to simulate the effects of changing the subsidies." (author-abstract, IAB-Doku) ((en)) Der Bericht analysiert die Wirkung von Subventionen zur Förderung des Ausbildungsplatzangebots in Betrieben (Teil der Ausbildung im Rahmen des dualen Systems) in Dänemark. Dazu werden Längsschnittdaten aus den Jahren 1980-1991 herangezogen, in denen verschiedene Förderungsprogramme das Ausbildungsplatzangebots und damit das Fachkräftepotential erhöhen sollten. (IAB)
Keywords: S 3.2 Unternehmen und Behörden; P 1.7 Benachteiligte; S 2.1.2 Berufsbildungsförderungsgesetz (BerBiFG); G 1.3.1.1 Ausbildungsstellenmarkt; G 1.2.2 Beschäftigungs- und Arbeitsverhältnisse; G 2.1.1 Ökonomie / Märkte; L 6.2.3 Evaluation; S 4.3.3 Effizienz & Effektivität des Berufsbildungswesens; I 2.2.1 Westeuropa; Ausbildungsplatzangebot; Förderung; Ausbildungsplatznachfrage; Betriebliche Berufsausbildung; Absolvent; Arbeitsmarktchance; Arbeitslosigkeit; Einkommen; Bildungsertrag; Subvention; Wirkungsforschung; Wirtschaftszweig; Kosten-Nutzen-Analyse; Quantitative Angaben; Dänemark; 1980-1991